Miliary fibromas in tuberous sclerosis complex. (23rd February 2021) - Cartron, A.M.; Buccine, D.; Treichel, A.M.; Lee, C.R.; Moss, J.; Darling, T.N.
Abstract: Background: Tuberous sclerosis complex (TSC) is a hamartoma syndrome characterized by multiple skin lesions, such as angiofibromas, shagreen patch and miliary fibromas (MiF). Objective: To determine the clinical and histological features of MiF. Methods: A retrospective analysis was conducted on 133 adults with TSC. Photography was used to characterize the appearance and location of MiF. Histological features in five skin samples from four individuals were evaluated by a board‐certified dermatopathologist. Results: MiF were observed in 19 of 133 (14%) individuals with TSC. MiF were 1‐ to 3‐mm skin‐coloured, sessile papules scattered on the back and rarely buttocks or thighs. Most were scattered in a bilaterally symmetric distribution, but others were asymmetric or associated with a shagreen patch. Histological features of MiF included expansion of the papillary and periadnexal dermis with variable hamartomatous abnormalities involving adjacent epithelial components. Conclusions: MiF are distinct from other cutaneous lesions in TSC such as shagreen patches and angiofibromas. Recognition of this entity is important in defining the spectrum of TSC disease and reassuring individuals with TSC that these lesions are benign.